Differential regulation of macrophage inflammatory activation by fibrin and fibrinogen. (1st January 2017) - Hsieh, Jessica Y.; Smith, Tim D.; Meli, Vijaykumar S.; Tran, Thi N.; Botvinick, Elliot L.; Liu, Wendy F.
Graphical abstract: Abstract: Fibrin is a major component of the provisional extracellular matrix formed during tissue repair following injury, and enables cell infiltration and anchoring at the wound site. Macrophages are dynamic regulators of this process, advancing and resolving inflammation in response to cues in their microenvironment. Although much is known about how soluble factors such as cytokines and chemokines regulate macrophage polarization, less is understood about how insoluble and adhesive cues, specifically the blood coagulation matrix fibrin, influence macrophage behavior. In this study, we observed that fibrin and its precursor fibrinogen elicit distinct macrophage functions. Culturing macrophages on fibrin gels fabricated by combining fibrinogen with thrombin stimulated secretion of the anti-inflammatory cytokine, interleukin-10 (IL-10). In contrast, exposure of macrophages to soluble fibrinogen stimulated high levels of inflammatory cytokine tumor necrosis factor alpha (TNF-α). Macrophages maintained their anti-inflammatory behavior when cultured on fibrin gels in the presence of soluble fibrinogen. In addition, adhesion to fibrin matrices inhibited TNF-α production in response to stimulation with LPS and IFN-γ, cytokines known to promote inflammatory macrophage polarization. Our data demonstrate that fibrin exerts a protective effect on macrophages, preventing inflammatory activation by stimuli including fibrinogen, LPS, and IFN-γ. Together, our study suggests that the presentation of fibrin(ogen) may be a key switch in regulating macrophage phenotype behavior, and this feature may provide a valuable immunomodulatory strategy for tissue healing and regeneration. Statement of Significance: Fibrin is a fibrous protein resulting from blood clotting and provides a provisional matrix into which cells migrate and to which they adhere during wound healing. Macrophages play an important role in this process, and are needed for both advancing and resolving inflammation. We demonstrate that culture of macrophages on fibrin matrices exerts an anti-inflammatory effect, whereas the soluble precursor fibrinogen stimulates inflammatory activation. Moreover, culture on fibrin completely abrogates inflammatory signaling caused by fibrinogen or known inflammatory stimuli including LPS and IFN-γ. Together, these studies show that the presentation of fibrin(ogen) is important for regulating a switch between macrophage pro- and anti-inflammatory behavior.